Mismatch repair and DNA polymerase δ proofreading prevent catastrophic accumulation of leading strand errors in cells expressing a cancer-associated DNA polymerase ϵ variant - Bulock, Chelsea R (Nucleic Acids Res, 2020)
Substitutions in the exonuclease domain of DNA polymerase ϵ cause ultramutated human tumors. Yeast and mouse mimics of the most common variant, P286R, produce mutator effects far exceeding the effect of Polϵ exonuclease deficiency. Yeast Polϵ-P301R has increased DNA polymerase activity, which could underlie its high mutagenicity. We aimed to understand the impact of this increased activity on the strand-specific role of Polϵ in DNA replication and the action of extrinsic correction systems that remove Polϵ errors. Using mutagenesis reporters spanning a well-defined replicon, we show that both exonuclease-deficient Polϵ (Polϵ-exo(−)) and Polϵ-P301R generate mutations in a strictly strand-specific manner, yet Polϵ-P301R is at least ten times more mutagenic than Polϵ-exo(−) at each location analyzed. Thus, the cancer variant remains a dedicated leading-strand polymerase with markedly low accuracy. We further show that P301R substitution is lethal in strains lacking Polδ proofreading or mismatch repair (MMR). Heterozygosity for pol2-P301R is compatible with either defect but causes strong synergistic increases in the mutation rate, indicating that Polϵ-P301R errors are corrected by Polδ proofreading and MMR. These data reveal the unexpected ease with which polymerase exchange occurs in vivo, allowing Polδ exonuclease to prevent catastrophic accumulation of Polϵ-P301R-generated errors on the leading strand.